1996
DOI: 10.1021/jp952774l
|View full text |Cite
|
Sign up to set email alerts
|

How Does Fe+ Activate C−C and C−H Bonds in Ethane? A Theoretical Investigation Using Density Functional Theory

Abstract: The potential energy surface (PES) corresponding to the reaction of the iron cation with ethane, which represents a prototype of the activation of C−C and C−H bonds in alkanes by transition metal cations, has been investigated employing the recently suggested hybrid density functional theory/Hartree−Fock method (B3LYP) combined with reasonably large one-particle basis sets. The performance of this computational approach has been calibrated against experimentally known Fe+−R binding energies of fragments R rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
156
0
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 176 publications
(172 citation statements)
references
References 49 publications
14
156
0
2
Order By: Relevance
“…The C-H insertion TS ͑DFT B3LYP and MCQDPT2͒ or C-H insertion TS and H 2 elimination TS ͓CCSD͑T͔͒ are the highest energy points en route to the products, with a net energy requirement of 5-9 kcal/mol, depending on the level of theory. In comparison, for the Co ϩ -and Fe ϩ -mediated elimination of H 2 from C 2 H 6 studied recently with DFT, 39 the C-H insertion TS was located below the entrance channel and the H 2 loss TS was the rate determining step. The higher relative energy of the C-H insertion TS in the Ti ϩ case might result from the more shallow potential well of its initial complex as compared to the Co ϩ and Fe ϩ analogs.…”
Section: ͑Ii͒mentioning
confidence: 89%
“…The C-H insertion TS ͑DFT B3LYP and MCQDPT2͒ or C-H insertion TS and H 2 elimination TS ͓CCSD͑T͔͒ are the highest energy points en route to the products, with a net energy requirement of 5-9 kcal/mol, depending on the level of theory. In comparison, for the Co ϩ -and Fe ϩ -mediated elimination of H 2 from C 2 H 6 studied recently with DFT, 39 the C-H insertion TS was located below the entrance channel and the H 2 loss TS was the rate determining step. The higher relative energy of the C-H insertion TS in the Ti ϩ case might result from the more shallow potential well of its initial complex as compared to the Co ϩ and Fe ϩ analogs.…”
Section: ͑Ii͒mentioning
confidence: 89%
“…There have only been a few detailed studies of potential energy surfaces ͑PES's͒ of reactions of transition metal atoms 56,57 and ions [58][59][60][61][62][63] with alkanes and other prototypical species. Blomberg and co-workers 56 performed complete active space self-consistent field ͑CASSCF͒ plus CI calculations on the reactions of Fe, Co, Ni, Rh, and Pd with CH 4 and C 2 H 6 , and concluded that the second row transition metals have higher barriers to insertion than do their first row analogs.…”
Section: Introductionmentioning
confidence: 99%
“…Double-dehydrogenation mechanisms in the reactions of M (M Fe, Co) with C 2 H 6 to form MC 2 H 2 2 H 2 were not reported in earlier studies by Holthausen et al [13,14] However, spontaneous double dehydrogenation was observed experimentally in the reactions of first-row transition-metal ions such as Sc and Ti with ethane. [55] Hence we also investigated double-dehydrogenation mechanism in the reaction of Sc with C 2 H 6 .…”
Section: Reaction Of Scmentioning
confidence: 87%
“…To explain the earlier experimental results and to generalize the mechanism postulated in Scheme 1 (middle), Holthausen et al reported two examples of theoretical investigations on the reactions of the late first-row transition-metal ions Fe and Co with ethane. [13,14] Their calculations indicated that: 1) These reactions process along both the CÀC and CÀH activation branches; 2) Each branch is composed of two elementary steps: C À C or C À H bond activation and subsequent isomerization of the inserted species by a b-H shift; 3) The rate-determining steps of the two branches are the isomerizations of the intermediate insertion products, rather than the initial CÀC or CÀH activation.…”
Section: Reaction Of Scmentioning
confidence: 99%